2019
DOI: 10.1108/bfj-02-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of banana peel powder (Musa balbisiana) on physicochemical and sensory properties of fish patty

Abstract: Purpose The purpose of this paper is to determine the physicochemical and sensory properties of fish patties added with banana peel powder (BPP), Musa balbisiana. Design/methodology/approach Four different fish patty formulations were produced containing 0 per cent (BPP0) (Control), 2 per cent (BPP2), 4 per cent (BPP4) and 6 per cent (BPP6) of BPP (M. balbisiana). Findings The addition of BPP was shown to improve the hardness, cooking yield, water holding capacity (WHC) and redness (a* value) as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
3
7
0
1
Order By: Relevance
“…Colour acceptance was significantly (p < 0.05) reduced in the treatments SBF4, SBF6, and BBF6, which may be due to the lower yellowness found in these treatments (Table 6). The results are in agreement with those of [36], where the inclusion of 4-6% of banana peel led to a decrease in the colour acceptance of the fish patties.…”
Section: Sensory Profilingsupporting
confidence: 91%
See 1 more Smart Citation
“…Colour acceptance was significantly (p < 0.05) reduced in the treatments SBF4, SBF6, and BBF6, which may be due to the lower yellowness found in these treatments (Table 6). The results are in agreement with those of [36], where the inclusion of 4-6% of banana peel led to a decrease in the colour acceptance of the fish patties.…”
Section: Sensory Profilingsupporting
confidence: 91%
“…Ref. [36] also reported results in line with the abovementioned, where the inclusion of banana peel did not affect the taste of fish patties.…”
Section: Sensory Profilingsupporting
confidence: 69%
“…In fish patties, the water holding capacity, toughness, cooking yield, redness, and fiber content were improved. However, harder texture, as detected by TA.XT plus texture analyzer, and the darker color were perceived when the banana peel flour of M. balbisiana was added (Zaini et al, 2019).…”
Section: Dietary Fiber Sourcementioning
confidence: 99%
“…However, the aforementioned authors observed that BPP caused a reduction in fat content, darkening, and a hard texture in chicken sausage. Likewise, in another study with cooked fish patties, banana peel powder (BPP, 2, 4, and 6%) of the Musa balbisiana variety caused an improvement in the cooking yield, water holding capacity, and dietary fiber content . Similar to the previous studies with banana peel in meat products, a harder texture and a significant reduction in color were observed in BPP treatments involving cooking by various cooking methods after thawing and consumption due to very low concentrations of the peel extract/powder added, pertaining to their health benefits mentioned previously.…”
Section: Bp In Meat and Meat Productsmentioning
confidence: 99%
“…Concerning sensorial/organoleptic properties, banana peel extract/powder primarily acts as a potential biological antioxidant that positively influences the sensorial/organoleptic characteristics of meat/meat products. Recently, Zaini et al assessed the effect of different banana peel powder concentrations on sensory aspects of fish patties. This study demonstrated that banana peel powder (2%) possesses a powerful ability compared to 4 and 6% incorporation to improve the texture and color, thereby increasing the overall acceptability of fish patties.…”
Section: Bp In Meat and Meat Productsmentioning
confidence: 99%